Creating children animation with Cube-It Toys - Woon, Arombo Yen Cheng (2018)
Evokube Junior is a newly developed product by the company PABensen that aims to develop every child’s cognitive learning abilities. In amidst of launching its product in crowdfunding platforms, an animated video could help kickstart its online presence and hope to establish a patronising user’s community. The Final Year Project report would elaborate the steps and thought process behind developing a short animation video. It would also highlight underlying factors integrated into the different phases of the project. Likewise, the report will conclude with a reflection, conclusion and showing necessary approach for the future path of the FYP.